Wheat Protein Hydrolysate Fortified With l‐Arginine Enhances Satiation Induced by the Capsaicinoid Nonivamide in Moderately Overweight Male Subjects. Issue 23 (2nd October 2019) - Stoeger, Verena; Lieder, Barbara; Riedel, Johanna; Schweiger, Kerstin; Hoi, Julia; Ruzsanyi, Veronika; Klieber, Martin; Rust, Petra; Hans, Joachim; Ley, Jakob P; Krammer, Gerhard E; Somoza, Veronika
Abstract : Scope: Increasing the intake of satiety‐enhancing food compounds represents a promising strategy for maintaining a healthy body weight. Recently, satiating effects for the capsaicinoid nonivamide have been demonstrated. As various proteins and amino acids have also been demonstrated to decrease energy intake, oral glucose tolerance test (oGTT)‐based bolus interventions of 75 g glucose + 0.15 mg nonivamide (NV control) are tested with/without combination of a wheat protein hydrolysate (WPH: 2 g) and/or l ‐arginine (ARG: 3.2 g) for their satiating effects in 27 moderately overweight male subjects. Methods and Results: Compared to NV control intervention, ARG and WPH + ARG treatment both reduce ( p  < 0.01) total calorie intake from a standardized breakfast by –5.9 ± 4.15% and –6.07 ± 4.38%, respectively. For the WPH + ARG intervention, increased mean plasma serotonin concentrations (AUC: 350 ± 218), quantitated by ELISA, and delayed gastric emptying, assessed by 13 C‐Na‐acetate breath test (−2.10 ± 0.51%, p  < 0.05), are demonstrated compared to NV control. Correlation analysis between plasma serotonin and gastric emptying reveals a significant association after WPH ± ARG intervention ( r  = –0.396, p  = 0.045). Conclusion: Combination of WPH and ARG enhances the satiating effect of nonivamide, providing opportunities to optimize satiating food formulations by low amounts of the individual food constituents. Abstract : A combination of satiating food constituents for enhancing satiety is a promising strategy for maintaining a healthy bodyweight. In this human intervention study, an l ‐arginine‐enriched wheat protein hydrolysate is demonstrated to further increase the satiating effect of nonivamide, a pungent pepper constituent, in healthy male volunteers when administered as a protein shake prior to an ad libitum breakfast.